DOES COVID-19 INFLUENCE THE IMPACT OF CORPORATE PARTNERSHIPS ON ORGANIZATIONAL PERFORMANCE? TAKE THE ELECTRONIC INDUSTRY INVESTIGATION METHOD OF ZHEJIANG PROVINCE AS AN EXAMPLE - Lin, Li-Wei; Zhang, Meng-yao; Zhang, Yun-Han (International Journal of Research -GRANTHAALAYAH, 2021)
Due to the influence of COVID-19, the global electronic industry has encountered problems in cooperation. Including a number of chip supply problems, so want to know whether the electronics industry executives have an impact on the company’s performance?This study through the investigation to the region in zhejiang province, 2020 local top one thousand electronic industry enterprise executives as questionnaire survey, the questionnaire (N = 331, excluding the reserved cross validity with data and error data, the number of available data and 195 pen, comply with the minimum sample demand, the main research object is for zhejiang area electronic industry as investigation object, and to establish its enterprise system agree with will affect the overall performance and profit of enterprise.Questionnaire design of this study was made through Likert seven-point scale, and reliability and validity verification analysis was conducted for this topic